Rare species and aliens: reconsidering non‐native plants in the management of natural areas. (22nd September 2016) - Dunwiddie, Peter W.; Rogers, Deborah L.
Abstract: Natural areas are often managed for the protection of native species and ecosystems. The presence of non‐native species is generally perceived to run counter to these objectives; thus, they are often controlled or tolerated but rarely deliberately favored. We suggest greater emphasis be placed on the role species play in ecological settings regardless of their origin, recognizing that only some non‐native plants are invasive, that the risk of causing ecological harm varies considerably, and that distributions will change as species migrate in response to climate change. We sense a disparity between the way this topic—conservation value of non‐native species—is addressed in the literature and how it is applied in management of natural areas. To encourage more discussion and consideration of appropriate roles for non‐natives in natural areas management, we present five case studies illustrating their value in the conservation of rare and endangered species, including Taylor's checkerspot and island marble butterflies, southwestern willow flycatcher, and the giant kangaroo rat. Our last case study describes a proposed conservation action for the rare Brewer spruce—that of assisted colonization, itself the creation of a non‐native for conservation purposes. Although we support continued avoidance of introducing invasives and a cautious treatment of non‐natives, we encourage those with responsibility for natural areas management to not only evaluate the threats posed by non‐natives, but to also consider their potential benefits in relation to management objectives.